Selectively cross-linked poly (lactide)/ethylene-glycidyl methacrylate-vinyl acetate thermoplastic elastomers with partial dual-continuous network-like structures and shape memory performances. (November 2016) - Xu, Pengwu; Ma, Piming; Cai, Xiaoxia; Song, Shiqiang; Zhang, Yong; Dong, Weifu; Chen, Mingqing
Graphical Abstract: Highlights: The epoxy groups facilitated the selective cross-link of only the EGVA phase. The TPVs exhibited partially dual-continuous network-like morphology. The TPVs showed good shape memory behavior. Superior mechanical properties and tunable hardness of the TPVs are achieved. Abstract: Bio-based poly (lactide)/ethylene-glycidyl methacrylate-vinyl acetate (PLA/EGVA) thermoplastic vulcanizates (TPVs) with partial dual-continuous network-like structures and shape memory property were made using methylhexahydrophthalic anhydride (MHHPA) as a cross-link agent. Epoxy groups of EGVA facilitated the selective cross-link of the EGVA phase in the PLA/EGVA blends, and two different chemical structures of the TPVs are identified based on the MHHPA content. The TPVs showed a special morphology evolution of the TPV, i.e., from sea-island-type to partial dual-continuous network-like morphology. As a consequence, the PLA/EGVA-based TPVs exhibited excellent shape memory property due to the strong resilience of the selectively cross-linked EGVA phase. The selective cross-link enhanced the complex viscosity ( η ∗ ), elasticity ( G ′) and the solid-like behavior of the PLA/EGVA-based TPVs. Meanwhile, low tensile set (30%), moderate tensile strength (12 MPa) and elongation at break (250%), and tunable hardness (60–75 Shore A) of the TPVs are achieved by tailoring the cross-link density and phase morphology.